2015
DOI: 10.1088/1742-6596/653/1/012081
|View full text |Cite
|
Sign up to set email alerts
|

Equation of state for tungsten over a wide range of densities and internal energies

Abstract: A caloric model, which describes the pressure-density-internal-energy relationship in a broad region of condensed-phase states, is applied for tungsten. As distinct from previously known caloric equations of state for this material, a new form of the cold-compression curve at T = 0 K is used. Thermodynamic characteristics along the cold curve and shock Hugoniots are calculated for the metal and compared with some theoretical results and experimental data available at high energy densities.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The EOS for matter is developed on the basis of the model [22][23][24], in which thermodynamic functions are related by the following general dependence:…”
Section: Eos Modelmentioning
confidence: 99%
“…The EOS for matter is developed on the basis of the model [22][23][24], in which thermodynamic functions are related by the following general dependence:…”
Section: Eos Modelmentioning
confidence: 99%
“…Various quantum-statistical cell models with the approximation of self-consistent field are widely used for development of equations of state [1][2][3]. The application of these approximations is even more valid, the higher the temperature and the density of matter [1].…”
Section: Introductionmentioning
confidence: 99%
“…For calculating of values σ sp and V /V 0 , a one-dimensional computational code was developed and used, which is based on Courant-Isaacson-Rees scheme for hydrodynamic equations [40,41]. The code is supplemented with wide-range equations of state of materials in question [42][43][44][45][46][47]. In calculations, it was suggested that the time profile of the ablation pressure pulse on the irradiated surface of the target replicates the profile of laser pulse intensity.…”
Section: Methods Of Determining Spall Strength and Strain Rate At Neg...mentioning
confidence: 99%